2008
DOI: 10.1080/10611860701878750
|View full text |Cite
|
Sign up to set email alerts
|

siRNA pool targeting different sites of human hepatitis B surface antigen efficiently inhibits HBV infection

Abstract: The main objective was to determine whether a pool of siRNAs targeting different regions of hepatitis B virus surface antigen (HBsAg) efficiently inhibits HBV infection. siRNAs targeting different regions of HBsAg were transfected into HBV-producing HepG2.2.15 cells and at 72h post transfection, the culture medium was collected for ELISA to determine HBsAg, while total RNA was isolated from the cells for real-time PCR. Three siRNA sequences which efficiently inhibited HBV infection were converted into small ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…In addition, most of the algorithms for shRNA sequence design actually comprise that of siRNA design and convert the siRNA into the shRNA sequence. In the present study, we have converted a potent siRNA targeting sequence into a shRNA sequence with success 7, 11. However, we also observed a loss of the silencing effect after converting the potent siRNA sequence into shRNA (data not show).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, most of the algorithms for shRNA sequence design actually comprise that of siRNA design and convert the siRNA into the shRNA sequence. In the present study, we have converted a potent siRNA targeting sequence into a shRNA sequence with success 7, 11. However, we also observed a loss of the silencing effect after converting the potent siRNA sequence into shRNA (data not show).…”
Section: Discussionmentioning
confidence: 52%
“…RNAi has been extensively used as a tool for gene silencing in cell lines and animal models 5, 6. In addition, it is also a promising approach for treating various acquired and genetic diseases 7, 8. Recently, we have tested the effects of siRNAs against inducible nitric oxide synthase (iNOS) genes on insulin producing β‐cell line (INS‐1E) and on human islets 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Following transfection of this shRNA, a 12-fold reduction of viral DNA after 30 passages over 8 months suggested reduced replicative capacity. Second, recent efforts have shown that the use of combination shRNAs is synergistic with respect to decreased production of HBsAg [40] as well as HBeAg, viral DNA, and cccDNA [41], and this strategy may prove useful to prevent against drug resistance. Third, these findings have been replicated in vitro.…”
Section: Rna Interferencementioning
confidence: 99%
“…In another study, Chen et al used siRNA pool targeting different regions of human hepatitis B surface antigen. The treatment of this siRNA pool showed efficient inhibition of hepatitis B surface antigens production at HBV-producing HepG2.2.15 cells [182]. Alternatively, co-silencing of multiple genes with siRNAs has also been used to achieve synergistic effect.…”
Section: Combinatorial Rnaimentioning
confidence: 99%